Adoption of Information and Communication Technology in Teaching and Learning in Secondary Schools in Nairobi County, Kenya - De', Kiage; Kaugi, Ephantus (African Journal of Education and Practice, 2023)
Purpose: The purpose of this study was to determine the adoption of information and communication technology (ICT) in teaching and learning in secondary schools in Nairobi County, Kenya. Specifically, the study aimed to evaluate the ICT adoption level, examine the teachers' training in the use of ICT, determine the ICT infrastructural capacity, and find out the teachers' perception of adopting ICT in public secondary schools in Nairobi County. Methodology: The study adopted a descriptive survey design. The target population comprised 475 teachers and 19 principals in secondary schools in Kasarani and Westland's sub-counties, which were randomly sampled. The sample comprised 164 teachers and 19 principals from 19 secondary schools drawn from the chosen sub-counties. Statistical Package for Social Sciences (SPSS version 25.0) was used to analyze quantitative data. Qualitative data were grouped into themes and analyzed thematically. Findings: The study found that secondary schools needed to be aware of the advantages of ICT tools to boost learning. Regarding ICT infrastructure, most schools examined had very few computers, which exacerbates the problem considering that most schools in these two sub-counties were county schools. According to the findings, most teachers and students needed easy access to computers for teaching and learning. Furthermore, the study revealed that most secondary school teachers had a positive attitude toward using ICT in teaching and learning. The study found that teachers supported the need for students to use ICT as a tool for practice and learning. Unique Contribution to Theory, Practice and Policy: The research indicated that appropriate administrative practices by school heads, teacher attitude, and the degree of teachers' ICT knowledge and abilities all significantly impacted the use of ICT in teaching and learning. The study recommends that secondary schools engage in technology education and training, and that the government and other education stakeholders support regular teacher ICT training to modify their view of using ICT tools in secondary school for teaching and learning. This study may be helpful for both the county and national governments in supporting secondary schools in terms of ICT.